Community Water Resource Management: A Case Study of Phraek Nam Daeng Community - Banchongsiri, Sujja; Keowan, Bumpen; Wechakit, Dusit; Yooprasert, Benchamas; Karndee, Paleerat (Electronic Journal of Open and Distance Innovative Learning (e-JODIL), 2015)
The objective of this research was to study lessons learned from community water resources management by the people of Phraek Nam Daeng Community. The research used the qualitative research methods of a discussion group forum, a learning seminar with community members, leaders and local officials, an area survey with record-taking of water management activities, and interviews with community leaders using a data recording form. Data analysis was done using qualitative research methods consisting of typological analysis, comparative analysis, relationship analysis, cause and effect analysis, and SWOT analysis. The results showed that water resource management was based primarily on the principle of stakeholder participation. Community research was used to give direction to development efforts. People in the community kept learning continuously. They applied local wisdom. Management was done by a group effort, and the community also worked in connection with a network of allies from within and outside the community. Water resource management was based on an integrated ecological model, utilizing structural, social and economic management tools.